Teachers’ perceptions of the barriers to STEM teaching in Qatar’s secondary schools: a structural equation modeling analysis - Sellami, Abdellatif; Santhosh, Malavika; Bhadra, Jolly; Ahmad, Zubair (Frontiers in Education, 2024)
Introduction Educators play a pivotal role in shaping students’ academic achievements, particularly in STEM (science, technology, engineering, and mathematics) fields. The instructional techniques employed by teachers significantly impact students’ decisions to pursue or persist in STEM disciplines. This research aims to explore the challenges faced by high school STEM teachers in Qatar in delivering effective STEM instruction. Methods Data was collected through a survey administered to 290 high school STEM teachers across thirty-nine schools in Qatar. The survey targeted teachers in the 11th and 12th grades. Structural Equation Modeling (SEM) was utilized to analyze the data and examine teachers’ perceived barriers to effective STEM instruction. Results The findings revealed various barriers hindering STEM instruction. These barriers were categorized into school-related, student-related, technology-related, and teaching-related factors. All the hypothesized teaching barriers [i.e., (student-related: β = –0.243, p < 0.001); (school-related: β = –0.122, p < 0.001), (technologyrelated: β = –0.123, p = 0.040); and (instruction-related: β = –0.112, p < 0.018)] were negatively related to teachers’ STEM teaching. Among the various obstacles, it appears that the most formidable challenges for high school STEM teachers are related to students (β = –0.243, p < 0.001). Discussion Understanding these barriers is crucial for informing educational policies and developing strategies to enhance STEM learning in Qatar’s high schools. Addressing these barriers is essential to provide adequate resources, professional development opportunities, and support systems. By addressing these challenges, Qatar can foster a conducive environment for effective STEM instruction, thereby nurturing a future generation of STEM professionals.